The Origin and Evolution of Giant Radio Galaxies - Garofalo, David (Frontiers in Astronomy and Space Sciences, 2022)
Giant radio galaxies are arguably the least understood of jetted active galactic nuclei (AGN). We propose that radio galaxies are the product of large mergers that do not involve radio galaxies or radio quasars, such as in merging spiral galaxies, while giant radio galaxies emerge from a merger involving a parent that in the not-too-distant past harbored a radio galaxy. Predictions following from this are an upper limit to the number fraction of giant radio galaxies to radio galaxies, lower average redshift for giant radio galaxies, a higher incidence of high excitation for giant radio galaxies compared with radio galaxies, and lower average prograde black hole spin values for giant radio galaxies compared to radio galaxies and to bright radio quiet quasars.